Evactinoporidae, a new family of Cystoporata (Bryozoa) from the Mississippian of North America: growth and functional morphology. (November 2019) - Yancey, Thomas E.; Wyse Jackson, Patrick N.; Sutton, Barry G.; Gottfried, Richard J.
Abstract: The morphology and growth habits of Evactinopora species of the Evactinoporidae (new family) are documented. This distinctive family of free-living bryozoans has a radial colony form at all growth stages. During a brief attachment phase on a hard substrate, the colony morphology grew as an expanding cone with vertical folds. Following detachment of the nascent colony from this hard substrate, it settled on soft sediment and the free-living expanding colony acquired a star-like form by producing slender outrigger rays. Continued growth produced a radial array of vertical vanes containing feeding autozooecia. The colony maintained a vertical orientation on soft sediment by means of outrigger rays and secretion of solid skeleton on the colony base that provided ballast. The radial growth pattern, outrigger rays, and vertical vanes developed as adaptive characters suitable for free-living life on soft sediment. North American species of Evactinopora are redefined and described taxonomically on the basis of zoarial and zooecial characters and a new species, Evactinopora mangeri, erected. The new family Evactinoporidae is established on the basis of the novel characters of early colony detachment from a hard surface, radial growth pattern through life, generation of outrigger rays, and growth of vertical vanes from the top of rays. UUID:http://zoobank.org/d2cf3b6d-72d2-49d5-afa0-c08710af7874